Heat conduction type aramid insulation paper-based material as well as preparation method and application thereof

By adding and modifying boron nitride nanosheets into the aramid insulating paper and using aramid nanofibers to build an orderly thermal conductivity path, the problem of low thermal conductivity of aramid insulating paper is solved, and more efficient thermal management and performance improvement is achieved.

CN119553547AActive Publication Date: 2025-03-04SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411590613.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-04
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing aramid insulating paper has low thermal conductivity, which causes equipment to fail to dissipate heat in time in high-frequency and high-power environments, reduces equipment performance and life, and may even cause fires.

Method used

By adding boron nitride nanosheets to aramid insulating paper, and through surface modification and the use of aramid nanofibers, the compatibility of boron nitride nanosheets and aramid fibers is improved, and an orderly thermal conductivity path is constructed.

Benefits of technology

It significantly improves the thermal conductivity of aramid insulating paper, reduces the interface thermal resistance, increases the retention rate of fillers, solves the problem of disordered thermal conductivity paths, and achieves more efficient thermal management.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553547A_ABST
    Figure CN119553547A_ABST
Patent Text Reader

Abstract

The invention discloses a heat-conducting aramid insulation paper-based material as well as a preparation method and application thereof. The preparation method of the heat-conducting aramid insulation paper-based material comprises the following steps: (1) introducing amino groups on the surfaces of boron nitride nanosheets to obtain aminated boron nitride nanosheets; (2) dissolving m-phenylenediamine in N, N-dimethylacetamide, then adding m-phthaloyl dichloride, then adding the amino boron nitride nanosheets, and carrying out a reaction to obtain a heat-conducting aramid polymer solution; (3) performing wet spinning on the heat-conducting aramid polymer solution to obtain heat-conducting aramid fibers; and (4) mixing the heat-conducting aramid fiber and the fibrid, and manufacturing the heat-conducting aramid insulation paper-based material. The amino boron nitride nanosheets are connected with amide groups among aramid macromolecules, so that the interfacial compatibility of the filler and the base material in the paper material is improved, and the strength and the heat-conducting property of the paper material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the cross field of papermaking industry and polymer materials, and particularly relates to a thermal conductive aramid insulation paper-based material and a preparation method and application thereof. Background Art

[0002] In recent years, with the increase in power density of electronic equipment and motors, the demand for heat dissipation performance of insulation materials is also rising. Aramid insulation paper is a high-performance insulation material with excellent thermal stability, mechanical strength and electrical insulation performance. It can be used as insulation material between turns, between phases, windings and wire ends of electrical equipment such as motors, generators and transformers. However, the thermal conductivity of aramid insulation paper is very low. The thermal conductivity of mature aramid insulation paper products is usually between 0.1 and 0.2W / (m·K). In a high-frequency and high-power environment, the heat accumulated rapidly in electrical equipment using aramid paper as insulation material will not be dissipated in time, which seriously reduces the performance and life of the equipment, and may cause equipment failure and fire, threatening social and personal safety.

[0003] Boron nitride nanosheets are two-dimensional sheet-like nanomaterials with a graphene-like structure. They can be obtained by chemical vapor deposition, mechanical exfoliation, and liquid phase exfoliation. Boron nitride nanosheets exhibit high thermal conductivity (400-2000Wm -1 K -1 ), excellent electrical insulation performance (10 14 -10 16 Ωcm), chemical stability and biocompatibility. Boron nitride nanosheets are an ideal thermal conductive filler in the field of thermal management and can be compounded with polymers to prepare thermal conductive polymer materials. In addition, boron nitride nanosheets have important applications in lubricants, high-temperature antioxidant coatings, catalytic carriers, drug delivery media and many other fields.

[0004] Improving the thermal conductivity of aramid insulation paper by adding boron nitride nanosheets is an effective method. Aramid paper materials are usually made of aramid fibrils and aramid chopped fibers in a certain ratio by wet papermaking. The aramid fibrils have a film-like appearance and microfibrils on the surface. They are usually used as filling and bonding materials in paper. The chopped fibers have a smooth and hard surface and are generally evenly dispersed in the paper as a skeleton. The specific preparation process of aramid paper-based materials includes: (1) washing and pulping of aramid fibrils; (2) dispersion of chopped fibers in water; (3) mixing of aramid fibrils and chopped fibers; (4) filtration; (5) hot pressing. Boron nitride nanosheets can be directly added to the pulp before filtration and left directly in the paper after filtration. However, since both aramid fibers and boron nitride nanosheets have smooth and chemically inert surfaces, this directly leads to low filler retention, the phenomenon of powder and slag falling off in the finished paper, and serious phonon scattering occurs at the interface between the filler and the substrate, which increases the problem of interfacial thermal resistance and is not conducive to the improvement of thermal conductivity. In addition, the poor dispersibility of boron nitride nanosheets leads to chaotic, disordered and inefficient heat conduction paths formed in the paper sheets. In order to achieve the thermal conductivity effect, the amount of filling has to be increased. In order to solve the above problems, surface modification of boron nitride nanosheets and the use of aramid nanofibers (ANF) instead of aramid fibers are two effective strategies (such as Chinese patents CN202310317355.2 and CN201810838115.6). Although these strategies improve the interfacial compatibility between the substrate and the filler, they do not solve the problems of chaotic and disordered heat conduction paths and high filling amounts. Improving the compatibility of boron nitride nanosheets and aramid fibers in a suitable manner and constructing orderly and efficient heat conduction paths are the key to obtaining aramid insulating paper-based materials with good thermal conductivity. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a thermally conductive aramid insulation paper-based material.

[0006] Another object of the present invention is to provide a thermally conductive aramid insulation paper-based material prepared by the above method.

[0007] Another object of the present invention is to provide an application of the above-mentioned thermal conductive aramid insulation paper-based material.

[0008] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a thermally conductive aramid insulation paper-based material comprises the following steps: (1) Preparation of amino boron nitride nanosheets: hexagonal boron nitride, urea and water are mixed and placed in a ball mill for ball milling. After the ball milling is completed, the excess urea is removed by washing with water, and then the mixture is ultrasonically dispersed in water. Large-sized unexfoliated boron nitride is first centrifuged to remove the solid. The lower layer is centrifuged again to collect the solid, and then freeze-dried to obtain amino boron nitride nanosheets. (2) Preparation of thermally conductive aramid polymer solution: The amino boron nitride nanosheets obtained in step (1) and N,N-dimethylacetamide are ultrasonically mixed to obtain an amino boron nitride nanosheet suspension; m-phenylenediamine is dissolved in N,N-dimethylacetamide under a protective gas atmosphere to obtain a m-phenylenediamine solution; then, isophthaloyl chloride is slowly added to the m-phenylenediamine solution multiple times under stirring conditions of -20°C to 0°C, and then the amino boron nitride nanosheet suspension is added, and the stirring speed is increased to carry out a condensation reaction, and the reaction temperature is controlled between 30°C and 60°C. After the pole climbing phenomenon occurs, the reaction is continued until the reaction is completed, and finally, an acid binding agent Ca(OH) is added. 2 Adjusting the pH to 4-9 to obtain a thermally conductive aramid polymer solution; (3) Preparation of thermally conductive aramid fiber: wet spinning the thermally conductive aramid polymer solution obtained in step (2), extruding from a spinning nozzle, and then coagulating, stretching, winding and heat-setting to obtain thermally conductive aramid fiber; (4) Wet papermaking: the thermally conductive aramid fibers obtained in step (3) are cut into short fibers, and then a dispersant and water are added to prepare a short fiber suspension; the precipitated fibrils are subjected to a decomposition treatment to prepare a precipitated fibril suspension; the short fiber suspension and the precipitated fibril suspension are then stirred and mixed uniformly, and wet papermaking is performed, followed by pressing and dehydration (filtering water), and hot pressing (forming) to obtain a thermally conductive aramid insulating paper-based material.

[0009] The mass ratio of hexagonal boron nitride, urea and water in step (1) is (1-10): (10-100): (1-100); preferably 1:30:12.

[0010] The water described in step (1) is preferably deionized water.

[0011] The ball mill described in step (1) is preferably a planetary ball mill.

[0012] The ball milling conditions in step (1) are: a rotation speed of 10 to 1000 rpm, and a ball milling time of 2 to 96 h; preferably: a rotation speed of 400 to 500 rpm, and a ball milling time of 20 to 48 h.

[0013] The ball milling balls used in the ball mill are 8mm agate balls and 4mm agate balls, with a mass ratio of 1:3 and a ball-to-material ratio of 3:2.

[0014] The water washing in step (1) can be carried out by vacuum filtration and repeated several times until the urea is cleaned.

[0015] The ultrasonic dispersion time in step (1) is 20 to 40 minutes, preferably 30 minutes.

[0016] In step (1), the conditions for removing large-sized unexfoliated boron nitride by centrifugation (low-speed centrifugation) are: rotation speed 1000-4000 rpm, and centrifugation time 20-40 min (preferably 30 min).

[0017] In step (1), the conditions for collecting the lower solid layer by centrifugation again (high-speed centrifugation) are: rotation speed 4000-8000 rpm, centrifugation time 30-60 min (preferably 50 min).

[0018] The concentration of the amino boron nitride nanosheet suspension in step (2) is 10-30 mg / mL, preferably 20 mg / mL.

[0019] The ultrasonic conditions in step (2) are: ultrasonic power 300-500W, ultrasonic time 20-40 min; preferably: ultrasonic power 400W, ultrasonic time 30 min.

[0020] In step (2), the purity of the two monomers, m-phenylenediamine and isophthaloyl chloride, is greater than 99.9%; the purity of N,N-dimethylacetamide is greater than 99.99%, and the water content is less than 500 ppm.

[0021] The molar ratio of m-phenylenediamine to isophthaloyl chloride in step (2) is (1-10):(1-10); preferably 1:(1.005-1.01); more preferably 1:1.005.

[0022] The protective gas in step (2) is nitrogen.

[0023] The concentration of the m-phenylenediamine solution in step (2) is 0.5 to 2 mol / L, preferably 0.8 to 1.2 mol / L, and more preferably 1.1 mol / L.

[0024] In step (2), the rotation speed when adding isophthaloyl chloride is 100 to 600 rpm, preferably 500 to 600 rpm.

[0025] The amount of the amino boron nitride nanosheets added in step (2) is 1 to 200% of the mass of m-phenylenediamine; preferably 5 to 20% of the mass of m-phenylenediamine.

[0026] In step (2), increasing the stirring speed is to increase the stirring speed to 1000-2000 rpm; preferably, increasing the stirring speed to 1000 rpm.

[0027] The conditions of the polycondensation reaction in step (2) are: initial temperature -20°C to 0°C (preferably -2°C to -6°C; more preferably -5°C), and total reaction time is 0.1 to 48 hours.

[0028] The time for continuing the reaction in step (2) is 1 to 10 hours, preferably 4 hours.

[0029] The pH adjustment in step (2) is to adjust the pH to 7.0-7.4.

[0030] The solid content of the thermally conductive aramid polymer solution in step (3) is 1% to 50%, preferably 10% to 20%, and more preferably 15%.

[0031] The wet spinning conditions described in step (3) are: the nozzle extrusion speed is 10 to 100 cm / min; the volume ratio of water to N,N-dimethylacetamide in the coagulation bath is (1 to 100): (1 to 100), the residence time in the coagulation bath is 1 to 500 s, the coagulation bath temperature is 20 to 60°C, the stretching ratio is 1.1 to 50 times, and the heat setting temperature is 50 to 600°C; preferably: the nozzle extrusion speed is 500 cm / min; the volume ratio of water to N,N-dimethylacetamide in the coagulation bath is 50:50, the residence time in the coagulation bath is 30 to 80 s, the coagulation bath temperature is 25 to 45°C, the stretching ratio is 2.4 to 3.7 times, and the heat setting temperature is 320°C.

[0032] The length of the chopped fibers in step (4) is 1 to 100 mm, preferably 3 to 6 mm.

[0033] The dispersant described in step (4) is preferably polyethylene oxide, and its viscosity average molecular weight is about 100,000.

[0034] The amount of the dispersant added in step (4) is 0.1 to 0.5% of the mass of the chopped fibers; preferably 0.3% of the mass of the chopped fibers.

[0035] The concentration of the chopped fiber suspension in step (4) is 0.01 to 10% by mass, preferably 0.1% by mass.

[0036] In step (4), the chopped fiber suspension can be obtained by treating with a wall breaking machine, and the treatment conditions are: 10000 rpm for 3 to 5 minutes (preferably 3 minutes).

[0037] The mass ratio of the chopped fibers to the precipitated fibers in step (4) is (1-10): (1-10); preferably (3-5): (5-7).

[0038] The concentration of the fiber suspension in step (4) is 0.01 to 10% by mass, preferably 0.1% by mass.

[0039] The rotation speed of the decomposition treatment in step (4) is 800-1200 rpm, preferably 1000 rpm.

[0040] The conditions for the squeezing and dehydration in step (4) are: squeezing and dehydration at 25°C and 0.2 MPa pressure for 5 min.

[0041] The hot pressing conditions in step (4) are: hot pressing temperature 50-600°C, hot pressing pressure 0.01-20Mpa, hot pressing time 0.1-48h; preferably: hot pressing temperature 200°C, hot pressing pressure 0.5Mpa, hot pressing time 30min.

[0042] The thermally conductive aramid insulation paper-based material described in step (4) has a weight of 1 to 100 g / m 2 ; preferably 50 to 70 g / m 2 .

[0043] A thermally conductive aramid insulation paper-based material is prepared by any of the methods described above.

[0044] Application of the thermally conductive aramid insulation paper-based material in insulation materials.

[0045] The thermally conductive aramid insulation paper-based material is used in multiple fields such as electrical equipment, electronic information, aerospace and automobile industry.

[0046] Compared with the prior art, the present invention has the following advantages and effects: 1. The thermally conductive aramid insulation paper-based material described in the present invention starts from the monomer polycondensation reaction, connects the amino boron nitride nanosheets to the aramid macromolecules through amide bonds, greatly improves the interfacial compatibility between the filler and the substrate, and reduces the interfacial thermal resistance. Furthermore, the polymer solution is prepared into thermally conductive aramid insulation fibers through wet spinning technology, and the boron nitride nanosheets are enriched and fixed on a single fiber, which solves the problems of poor dispersibility, low retention rate, and powder and slag falling of boron nitride nanosheets during paper production. Finally, the cut thermally conductive aramid insulation fibers are mixed with commercial aramid precipitated fibers to prepare thermally conductive aramid insulation paper, and the thermally conductive skeleton in the paper is constructed with the help of thermally conductive aramid insulation fibers to form an orderly and efficient thermal conductive path, thereby reducing the amount of boron nitride nanosheets added.

[0047] 2. In the present invention, hexagonal boron nitride and urea are used as basic raw materials, and amino groups are introduced on the surface of boron nitride nanosheets to increase the roughness and surface activity of the boron nitride nanosheets.

[0048] 3. The present invention utilizes the amide group connection between amino boron nitride nanosheets and aramid macromolecules to improve the interfacial compatibility of fillers and substrates in paper materials; utilizes wet spinning technology to prepare thermally conductive aramid fibers enriched with boron nitride nanosheets, and finally uses precipitated fibers to produce thermally conductive aramid insulating paper.

[0049] 4. The thermally conductive aramid insulation paper-based material prepared in the present invention can be widely used in many fields such as electrical equipment, electronic information, aerospace and automobile industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is a schematic diagram of the preparation process of the thermally conductive aramid insulation paper-based material in the present invention.

[0051] Figure 2 This is an atomic force microscope image of the amino boron nitride nanosheets used in the present invention.

[0052] Figure 3 This is a physical comparison diagram of hexagonal boron nitride and amino-bonded boron nitride nanosheets in Example 4 of the present invention; wherein A is hexagonal boron nitride; and B is amino-bonded boron nitride nanosheets.

[0053] Figure 4 This is a physical picture of the thermally conductive aramid fiber and the chopped short fibers cut out of Example 4 of the present invention; wherein A is the thermally conductive aramid fiber; and B is the chopped short fibers cut out of the thermally conductive aramid fiber.

[0054] Figure 5 This is a physical picture of the thermally conductive aramid insulation paper prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0055] The present invention is described in further detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not specified in the following examples are usually carried out according to conventional experimental conditions or according to the experimental conditions recommended by the manufacturer. Unless otherwise specified, each starting material in the preparation method of the present invention can be purchased from the market or prepared according to the prior art method.

[0056] The preparation process of the thermal conductive aramid insulation paper-based material of the present invention is as follows: Figure 1 shown.

[0057] The precipitated fibrils involved in the examples and comparative examples of the present invention were purchased from Ganzhou Longbang Material Technology Co., Ltd. and had a fineness of 2 denier.

[0058] The polyethylene oxide involved in the examples and comparative examples of the present invention was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and has a viscosity average molecular weight of about 100,000.

[0059] In the embodiments and comparative examples of the present invention, the tensile strength index is tested according to GB / T12914-2008; a thermal constant analyzer (Hot Disk TPS2200) is used to test the thermal conductivity of the composite paper, each sample is tested 5 times, and the average value is taken as the thermal conductivity.

[0060] Example 1 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of amino boron nitride nanosheets: Hexagonal boron nitride, urea and deionized water were uniformly mixed in a mass ratio of 1:30:12, and placed in an agate ball mill (the mass ratio of 8 mm agate balls to 4 mm agate balls was 1:3, and the ball-to-material ratio was 3:2 (mass ratio)). The planetary ball mill speed was 500 rpm, and the ball milling time was 20 h. After the ball milling was completed, the nanosheets were washed with a large amount of deionized water and filtered under vacuum. This process was repeated several times until the urea was cleaned. The paste obtained by filtration was filtered. The whole body was dispersed in deionized water by ultrasonication for 30 minutes, and the large pieces of boron nitride were removed by centrifugation at 1000 rpm for 30 minutes. The upper clear liquid was taken and centrifuged at 4000 rpm for 50 minutes. The lower solid was collected and freeze-dried to obtain the required amino boron nitride nanosheets. Finally, the amino boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed, and ultrasonicated for half an hour at a power of 400 W using an ultrasonic cell crusher to obtain an amino boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0061] (2) Preparation of thermal conductive aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm were used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction was 1:1.01; the specific steps were as follows: in a nitrogen environment, m-phenylenediamine was first dissolved in N,N-dimethylacetamide to prepare a 1.1 mol / L solution, and placed at a low temperature of -6°C, and isophthaloyl chloride was slowly added several times at a stirring rate of 500 rpm. After the isophthaloyl chloride was completely added, amino boron nitride nanosheet suspension was added, wherein the amount of amino boron nitride nanosheet added was equivalent to 10% of the mass of m-phenylenediamine, the stirring speed was increased to 1000 rpm, and the reaction temperature was controlled between 30°C and 60°C. After the pole climbing phenomenon appeared, the reaction was continued for 4 hours, and then the acid binding agent Ca(OH) was added. 2 The pH was adjusted to 7.0 to obtain a polymer solution.

[0062] (3) Preparation of thermally conductive aramid fiber: The solid content of the polymer solution prepared in step (2) was adjusted to 15%, the spinning nozzle speed was set to 50 cm / min, wet spinning was performed, the volume ratio of water and N,N-dimethylacetamide in the coagulation bath was 50:50, the fiber was kept in the coagulation bath for 30 seconds, the coagulation bath temperature was 45°C, the stretching ratio was 3.7 times, and after winding, it was heat-set at 320°C to obtain thermally conductive aramid fiber.

[0063] (4) Wet papermaking: The thermally conductive aramid fiber prepared in step (3) was cut into 3 mm short fibers, and with the help of a dispersant (polyethylene oxide, the amount was 0.3% of the mass of the short fibers) and water, a wall breaking machine was operated at 10000 rpm for 3 min to prepare a 0.1 wt% suspension (based on the mass of the short fibers). The precipitated fibers were weighed according to a mass ratio of short fibers to precipitated fibers of 40:60, and the precipitated fibers were dispersed in a fiber disintegrator at 1000 rpm to prepare a 0.1 wt% suspension; the short fibers and the precipitated fiber suspension were mixed and stirred evenly, and then wet papermaking was performed, and then the wet paper web was pressed and dehydrated at 25°C and 0.2 MPa pressure for 5 min, and then directly thermoformed (i.e., wet paper sheets were obtained by wet papermaking, and then dried and formed), the temperature was 200°C, the pressure was 0.5 MPa, the time was 30 min, and the paper weight was 54.3 g / m 2 , and finally a thermally conductive aramid insulation paper-based material was prepared.

[0064] The performance of the prepared thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 124.5 N*m / g and 0.372 W / (m*K), respectively.

[0065] Example 2 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of amino-boron nitride nanosheets: Hexagonal boron nitride, urea and deionized water were uniformly mixed in a mass ratio of 1:30:12, and then placed in an agate ball mill (the mass ratio of 8 mm agate balls to 4 mm agate balls was 1:3, and the ball-to-material ratio was 3:2). The planetary ball mill speed was 400 rpm, and the ball milling time was 48 h. After the ball milling was completed, it was washed with a large amount of deionized water and filtered under vacuum, and the process was repeated several times until the urea was cleaned. The paste obtained by filtration was dispersed in deionized water by ultrasonic for 30 min, and centrifuged at 3000 rpm for 30 min to remove large pieces of boron nitride. The upper clear liquid was taken and centrifuged at 7000 rpm for 50 min. The lower solid was collected and freeze-dried to obtain the desired amino-boron nitride nanosheets. Finally, the amino-boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed, and ultrasonicated for half an hour at a power of 400 W using an ultrasonic cell crusher to obtain an amino-boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0066] (2) Preparation of thermal conductive aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm were used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction was 1:1.008; the specific steps were as follows: in a nitrogen environment, m-phenylenediamine was first dissolved in N,N-dimethylacetamide to prepare a 1.2 mol / L solution, and placed at a low temperature of -5°C, and isophthaloyl chloride was slowly added several times at a stirring rate of 600 rpm. After the isophthaloyl chloride was completely added, amino boron nitride nanosheet suspension was added, wherein the amount of amino boron nitride nanosheet added was equivalent to 15% of the mass of m-phenylenediamine, the stirring speed was increased to 1000 rpm, and the reaction temperature was controlled between 30°C and 60°C. After the pole climbing phenomenon appeared, the reaction was continued for 4 hours, and then the acid binding agent Ca(OH) was added. 2 The pH was adjusted to 7.0 to obtain a polymer solution.

[0067] (3) Preparation of thermally conductive aramid fiber: The solid content of the polymer solution prepared in step (2) was adjusted to 15%, the spinning nozzle speed was set to 50 cm / min, wet spinning was performed, the volume ratio of water and N,N-dimethylacetamide in the coagulation bath was 50:50, the fiber was kept in the coagulation bath for 30 s, the coagulation bath temperature was 25°C, the stretching ratio was 3.3 times, and after winding, the fiber was heat-set at 320°C to obtain thermally conductive aramid fiber.

[0068] (4) Wet papermaking: The thermally conductive aramid fiber prepared in step (3) was cut into 6 mm short fibers, and with the help of a dispersant (polyethylene oxide, the amount was 0.3% of the mass of the short fibers) and water, a wall breaking machine was used at 10000 rpm for 3 min to prepare a 0.1 wt % suspension (based on the mass of the short fibers). The precipitated fibers were weighed according to a mass ratio of short fibers to precipitated fibers of 30:70, and the precipitated fibers were dispersed in a fiber disintegrator at 1000 rpm to prepare a 0.1 wt % suspension; the short fibers and the precipitated fiber suspension were mixed and stirred evenly, and then wet papermaking was performed, and then the wet paper web was pressed and dehydrated at 25°C and 0.2 MPa pressure for 5 min, and then directly thermoformed (i.e., wet paper sheets were obtained by wet papermaking, and then dried and formed), the temperature was 200°C, the pressure was 0.5 MPa, the time was 30 min, and the paper weight was 60.6 g / m 2 , and finally a thermally conductive aramid insulation paper-based material was prepared.

[0069] The performance of the prepared thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 97.3 N*m / g and 0.396 W / (m*K), respectively.

[0070] Example 3 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of amino-boron nitride nanosheets: Hexagonal boron nitride, urea and deionized water were uniformly mixed in a mass ratio of 1:20:10 and placed in an agate ball mill (the mass ratio of 8 mm agate balls to 4 mm agate balls was 1:3, and the ball-to-material ratio was 3:2). The planetary ball mill speed was 500 rpm and the ball milling time was 20 h. After the ball milling was completed, the mixture was washed with a large amount of deionized water and filtered under vacuum. This process was repeated several times until the urea was cleaned. The paste obtained by filtration was dispersed in deionized water by ultrasonication for 30 min, and centrifuged at 1000 rpm for 30 min to remove large pieces of boron nitride. The upper clear liquid was taken and centrifuged at 4000 rpm for 50 min. The lower solid was collected and freeze-dried to obtain the desired amino-boron nitride nanosheets. Finally, the amino-boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed and ultrasonicated at 400 W for half an hour using an ultrasonic cell crusher to obtain an amino-boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0071] (2) Preparation of thermal conductive aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm were used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction was 1:1.01; the specific steps were as follows: in a nitrogen environment, m-phenylenediamine was first dissolved in N,N-dimethylacetamide to prepare a 0.8 mol / L solution, and placed at a low temperature of -2°C, and isophthaloyl chloride was slowly added several times at a stirring rate of 500 rpm. After the isophthaloyl chloride was completely added, amino boron nitride nanosheet suspension was added, wherein the amount of amino boron nitride nanosheet added was equivalent to 5% of the mass of m-phenylenediamine, the stirring speed was increased to 1000 rpm, and the reaction temperature was controlled between 30°C and 60°C. After the pole climbing phenomenon appeared, the reaction was continued for 4 hours, and then the acid binding agent Ca(OH) was added. 2 The pH was adjusted to 7.4 to obtain a polymer solution.

[0072] (3) Preparation of thermally conductive aramid fiber: The solid content of the polymer solution prepared in step (2) was adjusted to 15%, the spinning nozzle speed was set to 50 cm / min, wet spinning was performed, the volume ratio of water and N,N-dimethylacetamide in the coagulation bath was 50:50, the fiber was kept in the coagulation bath for 30 seconds, the coagulation bath temperature was 25°C, the stretching ratio was 2.4 times, and after winding, the fiber was heat-set at 320°C to obtain thermally conductive aramid fiber.

[0073] (4) Wet papermaking: The thermally conductive aramid fiber prepared in step (3) was cut into 3 mm short fibers, and with the help of a dispersant (polyethylene oxide, the amount was 0.3% of the mass of the short fibers) and water, a wall breaking machine was used at 10000 rpm for 3 min to prepare a 0.1 wt % suspension (based on the mass of the short fibers). The precipitated fibers were weighed according to a mass ratio of 50:50 between the short fibers and the precipitated fibers, and the precipitated fibers were dispersed in a fiber disintegrator at 1000 rpm to prepare a 0.1 wt % suspension; the short fibers and the precipitated fiber suspension were mixed and stirred evenly, and then wet papermaking was performed, and then the wet paper web was pressed and dehydrated at 25°C and 0.2 MPa pressure for 5 min, and then directly thermoformed (i.e., the wet paper was obtained by wet papermaking, and then dried and formed), the temperature was 200°C, the pressure was 0.5 MPa, the time was 30 min, and the paper weight was 54.8 g / m 2 , and finally a thermally conductive aramid insulation paper-based material was prepared.

[0074] The performance of the prepared thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 101.6 N*m / g and 0.237 W / (m*K), respectively.

[0075] Example 4 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of amino boron nitride nanosheets: Hexagonal boron nitride, urea and deionized water were uniformly mixed in a mass ratio of 1:30:12, and then placed in an agate ball mill (the mass ratio of 8 mm agate balls to 4 mm agate balls was 1:3, and the ball-to-material ratio was 3:2). The planetary ball mill speed was 500 rpm, and the ball milling time was 32 h. After the ball milling, the mixture was washed with a large amount of deionized water and filtered under vacuum, and the process was repeated several times until the urea was cleaned. The paste obtained by filtration was dispersed in deionized water by ultrasonication for 30 min, and centrifuged at 4000 rpm for 30 min to remove large pieces of boron nitride. The upper clear liquid was taken, and centrifuged at 8000 rpm for 50 min. The lower solid was collected and freeze-dried to obtain the desired amino boron nitride nanosheets ( Figure 2 , Figure 3 ), and finally, the amino boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed, and ultrasonicated for half an hour at a power of 400 W using an ultrasonic cell crusher to obtain an amino boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0076] (2) Preparation of thermal conductive aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm were used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction was 1:1.005; the specific steps were as follows: in a nitrogen environment, m-phenylenediamine was first dissolved in N,N-dimethylacetamide to prepare a 1.0 mol / L solution, and placed at a low temperature of -5°C, and isophthaloyl chloride was slowly added several times at a stirring rate of 500 rpm. After the isophthaloyl chloride was completely added, amino boron nitride nanosheet suspension was added, wherein the amount of amino boron nitride nanosheet added was equivalent to 20% of the mass of m-phenylenediamine, the stirring speed was increased to 1000 rpm, and the reaction temperature was controlled between 30°C and 60°C. After the pole climbing phenomenon appeared, the reaction was continued for 4 hours, and then the acid binding agent Ca(OH) was added. 2 The pH was adjusted to 7.0 to obtain a polymer solution.

[0077] (3) Preparation of thermally conductive aramid fiber: The solid content of the polymer solution prepared in step (2) was adjusted to 19%, the spinning nozzle speed was set to 50 cm / min, wet spinning was performed, the volume ratio of water and N,N-dimethylacetamide in the coagulation bath was 50:50, the fiber was kept in the coagulation bath for 80 s, the coagulation bath temperature was 25°C, the stretching ratio was 3.3 times, and after winding, the fiber was heat-set at 320°C to obtain thermally conductive aramid fiber.

[0078] (4) Wet papermaking: The thermally conductive aramid fiber prepared in step (3) is cut into 6 mm short fibers ( Figure 4 ), with the help of dispersant (polyethylene oxide, the amount is 0.3% of the mass of short-cut fibers) and water, the wall breaking machine is 10000rpm, 3min, and a 0.1 wt% suspension (based on the mass of short-cut fibers) is prepared. According to the mass ratio of short-cut fibers and precipitated fibers of 40:60, the precipitated fibers are weighed, and the precipitated fibers are dispersed by a fiber disintegrator at 1000rpm to prepare a 0.1 wt% suspension; the short-cut fibers and precipitated fiber suspension are mixed, stirred evenly, and then wet-made papermaking is performed, and then the wet paper web is pressed and dehydrated at 25°C and 0.2MPa pressure for 5 min, and then directly thermoformed (that is, aramid wet paper sheets are obtained by wet papermaking, and then dried and formed), the temperature is 200°C, the pressure is 0.5Mpa, the time is 30min, and the paper weight is 64.3g / m 2 , and finally prepared a thermally conductive aramid insulation paper-based material ( Figure 5 ).

[0079] The performance of the prepared thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 88.4 N*m / g and 0.541 W / (m*K), respectively.

[0080] Comparative Example 1 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of amino-boron nitride nanosheets: Hexagonal boron nitride, urea and deionized water were uniformly mixed in a mass ratio of 1:30:12, and then placed in an agate ball mill (the mass ratio of 8 mm agate balls to 4 mm agate balls was 1:3, and the ball-to-material ratio was 3:2). The planetary ball mill speed was 500 rpm, and the ball milling time was 32 h. After the ball milling was completed, it was washed with a large amount of deionized water and filtered under vacuum, and the process was repeated several times until the urea was cleaned. The paste obtained by filtration was dispersed in deionized water by ultrasonic for 30 min, and centrifuged at 4000 rpm for 30 min to remove large pieces of boron nitride. The upper clear liquid was taken and centrifuged at 8000 rpm for 50 min. The lower solid was collected and freeze-dried to obtain the desired amino-boron nitride nanosheets. Finally, the amino-boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed, and ultrasonic cell crusher was used to ultrasonicate for half an hour at a power of 400 W to obtain an amino-boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0081] (2) Preparation of aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm are used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction is 1:1.005; the specific steps are as follows: in a nitrogen environment, m-phenylenediamine is first dissolved in N,N-dimethylacetamide to prepare a 1.0 mol / L solution, and the solution is placed at a low temperature of -5°C, and isophthaloyl chloride is slowly added multiple times at a stirring rate of 500 rpm. After the isophthaloyl chloride is completely added, the stirring rate is increased to 1000 rpm, and the reaction temperature is controlled between 30°C and 60°C. After the pole climbing phenomenon occurs, the reaction is continued for 4 hours, and then the acid binding agent Ca(OH) is added. 2 The pH was adjusted to 7.0 to obtain a polymer solution.

[0082] (3) Preparation of aramid fiber: The solid content of the polymer solution prepared in step (2) was adjusted to 19%. The spinning nozzle speed was set to 50 cm / min, and wet spinning was performed. The volume ratio of water and N,N-dimethylacetamide in the coagulation bath was 50:50. The fiber stayed in the coagulation bath for 80 seconds. The coagulation bath temperature was 25°C, the stretching ratio was 3.3 times, and after winding, the fiber was heat-set at 320°C to obtain aramid fiber.

[0083] (4) Wet papermaking: The aramid fibers prepared in step (3) were cut into 6 mm short fibers and, with the help of a dispersant (polyethylene oxide, 0.3% by weight of the short fibers) and water, were processed in a wall breaking machine at 10,000 rpm for 3 min to prepare a 0.1 wt % suspension (based on the weight of the short fibers). The precipitated fibers are weighed according to a mass ratio of chopped fibers to precipitated fibers of 40:60, and the precipitated fibers are dispersed in a fiber disintegrator at 1000 rpm to prepare a 0.1 wt % suspension; the chopped fibers, precipitated fibers and the amino boron nitride nanosheet suspension prepared in step (1) are mixed, and the amount of amino boron nitride nanosheet added is equivalent to 20% of the mass of the intermediate phenylenediamine in step (2); after being stirred evenly, wet papermaking is performed, and then the wet paper web is pressed and dehydrated at 25° C. and 0.2 MPa pressure for 5 min, and then directly thermoformed (i.e., aramid wet paper sheets are obtained by wet papermaking, and then dried and formed) at a temperature of 200° C., a pressure of 0.5 MPa, a time of 30 min, and a paper weight of 64.3 g / m 2 , and finally a thermally conductive aramid insulation paper-based material was prepared.

[0084] The performance of the prepared thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 70.3 N*m / g and 0.271 W / (m*K), respectively.

[0085] Comparative Example 2 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of boron nitride nanosheet dispersion: Boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed and ultrasonicated for one hour at a power of 400 W using an ultrasonic cell crusher to obtain a boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0086] (2) Preparation of aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm are used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction is 1:1.005; the specific steps are as follows: in a nitrogen environment, m-phenylenediamine is first dissolved in N,N-dimethylacetamide to prepare a 1.0 mol / L solution, and the solution is placed at a low temperature of -5°C, and isophthaloyl chloride is slowly added multiple times at a stirring rate of 500 rpm. After the isophthaloyl chloride is completely added, the stirring rate is increased to 1000 rpm, and the reaction temperature is controlled between 30°C and 60°C. After the pole climbing phenomenon occurs, the reaction is continued for 4 hours, and then the acid binding agent Ca(OH) is added. 2 The pH was adjusted to 7.0 to obtain a polymer solution.

[0087] (3) Preparation of aramid fiber: The solid content of the polymer solution prepared in step (2) was adjusted to 19%. The spinning nozzle speed was set to 50 cm / min, and wet spinning was performed. The volume ratio of water and N,N-dimethylacetamide in the coagulation bath was 50:50. The fiber stayed in the coagulation bath for 80 seconds. The coagulation bath temperature was 25°C, the stretching ratio was 3.3 times, and after winding, the fiber was heat-set at 320°C to obtain aramid fiber.

[0088] (4) Wet papermaking: The aramid fibers prepared in step (3) were cut into 6 mm short fibers and, with the help of a dispersant (polyethylene oxide, 0.3% by weight of the short fibers) and water, were processed in a wall breaking machine at 10,000 rpm for 3 min to prepare a 0.1 wt % suspension (based on the weight of the short fibers). The precipitated fibers are weighed according to a mass ratio of chopped fibers to precipitated fibers of 40:60, and the precipitated fibers are dispersed in a fiber disintegrator at 1000 rpm to prepare a 0.1 wt % suspension; the chopped fibers, precipitated fibers and the boron nitride nanosheet suspension prepared in step (1) are mixed, and the amount of boron nitride nanosheets added is equivalent to 20% of the mass of the intermediate phenylenediamine in step (2); after being stirred evenly, wet papermaking is performed, and then the wet paper web is pressed and dehydrated at 25° C. and 0.2 MPa pressure for 5 min, and then directly thermoformed (i.e., aramid wet paper sheets are obtained by wet papermaking, and then dried and formed) at a temperature of 200° C., a pressure of 0.5 MPa, a time of 30 min, and a paper weight of 64.3 g / m 2 , and finally a thermally conductive aramid insulation paper-based material was prepared.

[0089] The performance of the prepared thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 66.1 N*m / g and 0.142 W / (m*K), respectively.

[0090] Comparative Example 3 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of amino-boron nitride nanosheets: Hexagonal boron nitride, urea and deionized water were uniformly mixed in a mass ratio of 1:30:10 and placed in an agate ball mill (the mass ratio of 8 mm agate balls to 4 mm agate balls was 1:3, and the ball-to-material ratio was 3:2). The planetary ball mill speed was 500 rpm and the ball milling time was 20 h. After the ball milling was completed, it was washed with a large amount of deionized water and filtered under vacuum. This process was repeated several times until the urea was cleaned. The paste obtained by filtration was dispersed in deionized water by ultrasonication for 30 min, and centrifuged at 1000 rpm for 30 min to remove large pieces of boron nitride. The upper clear liquid was taken and centrifuged at 4000 rpm for 50 min. The lower solid was collected and freeze-dried to obtain the desired amino-boron nitride nanosheets. Finally, the amino-boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed and ultrasonicated at 400 W for half an hour using an ultrasonic cell crusher to obtain an amino-boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0091] (2) Preparation of aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm were used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction was 1:1.01; the specific steps were as follows: in a nitrogen environment, m-phenylenediamine was first dissolved in N,N-dimethylacetamide to prepare a 1.1 mol / L solution, and the solution was placed at a low temperature of -6°C, and isophthaloyl chloride was slowly added several times at a stirring rate of 500 rpm. After the isophthaloyl chloride was completely added, the stirring speed was increased to 1000 rpm, and the reaction temperature was controlled between 30°C and 60°C. After the pole climbing phenomenon appeared, the reaction was continued for 4 hours, and then the acid binding agent Ca(OH) was added. 2 The pH was adjusted to 7.0 to obtain a polymer solution.

[0092] (3) Preparation of thermally conductive aramid fiber: first, add the amino boron nitride nanosheet suspension prepared in step (1) to the polymer solution prepared in step (2), wherein the amount of amino boron nitride nanosheet added is controlled to be 10% of the mass of m-phenylenediamine, and then adjust the solid content of the polymer solution to 15%. Set the spinning nozzle speed to 50 cm / min, perform wet spinning, and use a 50:50 volume ratio of water and N,N-dimethylacetamide in the coagulation bath. Stay in the coagulation bath for 30 seconds. The coagulation bath temperature is 45°C, the stretching ratio is 3.7 times, and after winding, heat setting is performed at 320°C to obtain a thermally conductive aramid fiber.

[0093] (4) Wet papermaking: The thermally conductive aramid fiber prepared in step (3) was cut into 3 mm short fibers, and with the help of a dispersant (polyethylene oxide, the amount was 0.3% of the mass of the short fibers) and water, a wall breaking machine was used at 10000 rpm for 3 min to prepare a 0.1 wt % suspension (based on the mass of the short fibers). The precipitated fibers were weighed according to a mass ratio of short fibers to precipitated fibers of 60:40, and the precipitated fibers were dispersed in a fiber disintegrator at 1000 rpm to prepare a 0.1 wt % suspension; the short fibers and the precipitated fiber suspension were mixed and stirred evenly, and then wet papermaking was performed, and then the wet paper web was pressed and dehydrated at 25°C and 0.2 MPa pressure for 5 min, and then directly thermoformed (i.e., wet paper sheets were obtained by wet papermaking, and then dried and formed), the temperature was 200°C, the pressure was 0.5 MPa, the time was 30 min, and the paper weight was 54.3 g / m 2 , and finally a thermally conductive aramid insulation paper-based material was prepared.

[0094] The performance of the prepared thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 73.3 N*m / g and 0.293 W / (m*K), respectively.

[0095] Comparative Example 4 A thermally conductive aramid insulation paper-based material, the preparation method of which is as follows: (1) Preparation of boron nitride nanosheet dispersion: Boron nitride nanosheets and N,N-dimethylacetamide were uniformly mixed and ultrasonicated for one hour at a power of 400 W using an ultrasonic cell crusher to obtain a boron nitride nanosheet suspension with a mass concentration of 20 mg / mL.

[0096] (2) Preparation of aramid polymer solution: m-phenylenediamine and isophthaloyl chloride with a purity of more than 99.9%, and N,N-dimethylacetamide solution with a purity of more than 99.99% and a water content of less than 500 ppm were used; the molar ratio of m-phenylenediamine and isophthaloyl chloride involved in the reaction was 1:1.01; the specific steps were as follows: in a nitrogen environment, m-phenylenediamine was first dissolved in N,N-dimethylacetamide to prepare a 1.1 mol / L solution, and the solution was placed at a low temperature of -6°C, and isophthaloyl chloride was slowly added several times at a stirring rate of 500 rpm. After the isophthaloyl chloride was completely added, the stirring speed was increased to 1000 rpm, and the reaction temperature was controlled between 30°C and 60°C. After the pole climbing phenomenon appeared, the reaction was continued for 4 hours, and then the acid binding agent Ca(OH) was added. 2 The pH was adjusted to 7.0 to obtain a polymer solution.

[0097] (3) Preparation of thermally conductive aramid fiber: First, add the boron nitride nanosheet suspension prepared in step (1) to the polymer solution prepared in step (2), and control the amount of boron nitride nanosheets added to 10% of the mass of m-phenylenediamine. Then adjust the solid content of the polymer solution to 15%. Set the spinning nozzle speed to 50 cm / min, perform wet spinning, and the volume ratio of water and N,N-dimethylacetamide in the coagulation bath is 50:50. Stay in the coagulation bath for 30 seconds. The coagulation bath temperature is 45°C, the stretching ratio is 3.7 times, and after winding, heat setting is performed at 320°C to obtain thermally conductive aramid fiber.

[0098] (4) Wet papermaking: The thermally conductive aramid fiber prepared in step (3) was cut into 3 mm short fibers, and with the help of a dispersant (polyethylene oxide, the amount was 0.3% of the mass of the short fibers) and water, a wall breaking machine was used at 10000 rpm for 3 min to prepare a 0.1 wt % suspension (based on the mass of the short fibers). The precipitated fibers were weighed according to a mass ratio of short fibers to precipitated fibers of 60:40, and the precipitated fibers were dispersed in a fiber disintegrator at 1000 rpm to prepare a 0.1 wt % suspension; the short fibers and the precipitated fiber suspension were mixed and stirred evenly, and then wet papermaking was performed, and then the wet paper web was pressed and dehydrated at 25°C and 0.2 MPa pressure for 5 min, and then directly thermoformed (i.e., wet paper sheets were obtained by wet papermaking, and then dried and formed), the temperature was 200°C, the pressure was 0.5 MPa, the time was 30 min, and the paper weight was 54.3 g / m 2 , and finally a thermally conductive aramid insulation paper-based material was prepared.

[0099] The performance of the thermally conductive aramid insulation paper-based material was tested, and the tensile strength index and thermal conductivity were 61.4 N*m / g and 0.197 W / (m*K), respectively.

[0100] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a thermally conductive aramid insulation paper-based material, characterized in that: The steps include: (1) Preparation of amino boron nitride nanosheets: hexagonal boron nitride, urea and water are mixed and placed in a ball mill for ball milling. After the ball milling is completed, the excess urea is removed by washing with water, and then the mixture is ultrasonically dispersed in water. Large-sized unexfoliated boron nitride is first centrifuged to remove the solid. The lower layer is centrifuged again to collect the solid, and then freeze-dried to obtain amino boron nitride nanosheets. (2) Preparation of thermally conductive aramid polymer solution: The amino boron nitride nanosheets obtained in step (1) and N,N-dimethylacetamide are ultrasonically mixed to obtain an amino boron nitride nanosheet suspension; under a protective gas atmosphere, m-phenylenediamine is dissolved in N,N-dimethylacetamide to obtain a m-phenylenediamine solution; then, isophthaloyl chloride is slowly added to the m-phenylenediamine solution multiple times under stirring conditions of -20°C to 0°C, and then the amino boron nitride nanosheet suspension is added, and the stirring speed is increased to carry out a condensation reaction, and the reaction temperature is controlled between 30°C and 60°C. After the pole climbing phenomenon occurs, the reaction is continued until the reaction is completed, and finally, an acid binding agent Ca(OH)2 is added to adjust the pH to 4 to 9 to obtain a thermally conductive aramid polymer solution; (3) Preparation of thermally conductive aramid fiber: wet spinning the thermally conductive aramid polymer solution obtained in step (2), extruding from a spinning nozzle, and then coagulating, stretching, winding and heat-setting to obtain thermally conductive aramid fiber; (4) Wet papermaking: cutting the thermally conductive aramid fibers obtained in step (3) into short fibers, and then adding a dispersant and water to prepare a short fiber suspension; The fibrides are subjected to decomposition treatment to prepare a fibrides suspension; Then the short-cut fiber suspension and the precipitated fiber suspension are stirred and mixed evenly, and wet papermaking, pressing and dehydration, and hot pressing are performed to obtain a thermal conductive aramid insulation paper-based material.

2. The method according to claim 1, characterized in that: The mass ratio of hexagonal boron nitride, urea and water in step (1) is 1-10:10-100:1-100; The molar ratio of m-phenylenediamine to isophthaloyl chloride in step (2) is 1-10:1-10; The amount of the amino boron nitride nanosheets added in step (2) is 1 to 200% of the mass of m-phenylenediamine; The solid content of the thermally conductive aramid polymer solution in step (3) is 1% to 50%; The mass ratio of the chopped fibers to the precipitated fibers in step (4) is 1-10:1-10.

3. The method according to claim 2, characterized in that: The mass ratio of hexagonal boron nitride, urea and water in step (1) is 1:30:12; The molar ratio of m-phenylenediamine to isophthaloyl chloride in step (2) is 1:1.005-1.01; The amount of the amino boron nitride nanosheets added in step (2) is 5 to 20% of the mass of m-phenylenediamine; The solid content of the thermally conductive aramid polymer solution in step (3) is 10% to 20%; The mass ratio of the chopped fibers to the precipitated fibers in step (4) is 3-5:5-7.

4. The method according to claim 1, characterized in that: The concentration of the amino boron nitride nanosheet suspension in step (2) is 10-30 mg / mL; The concentration of the m-phenylenediamine solution in step (2) is 0.5 to 2 mol / L; The dispersant in step (4) is polyethylene oxide; The amount of the dispersant added in step (4) is 0.1 to 0.5% of the mass of the chopped fibers; The concentration of the chopped fiber suspension in step (4) is 0.01 to 10% by mass; The concentration of the fiber suspension in step (4) is 0.01 to 10% by mass.

5. The method according to claim 1, characterized in that: The wet spinning conditions described in step (3) are as follows: the nozzle extrusion speed is 10 to 100 cm / min; the volume ratio of water to N,N-dimethylacetamide in the coagulation bath is 1 to 100:1 to 100, the residence time in the coagulation bath is 1 to 500 s, the coagulation bath temperature is 20 to 60° C., the stretching ratio is 1.1 to 50 times, and the heat setting temperature is 50 to 600° C.

6. The method according to claim 1, characterized in that: The ball milling conditions in step (1) are: a rotation speed of 10 to 1000 rpm and a ball milling time of 2 to 96 hours; In step (1), the conditions for centrifugation to remove large-sized unpeeled boron nitride are: rotation speed 1000-4000 rpm, centrifugation time 20-40 min; In step (1), the conditions for collecting the lower solid layer by centrifugation again are: rotation speed 4000-8000 rpm, centrifugation time 30-60 min; In step (2), the rotation speed when adding isophthaloyl chloride is 100 to 600 rpm; In step (2), increasing the stirring speed is to increase the stirring speed to 1000-2000 rpm.

7. The method according to claim 1, characterized in that: The ultrasonic dispersion time in step (1) is 20 to 40 minutes; The ultrasonic conditions in step (2) are: ultrasonic power 300-500W, ultrasonic time 20-40 min; The reaction time in step (2) is 1 to 10 hours; The pH adjustment in step (2) is to adjust the pH to 7.0-7.4; The length of the chopped fibers in step (4) is 1 to 100 mm; The conditions for the squeezing and dehydration in step (4) are: squeezing and dehydration at 25°C and 0.2 MPa pressure for 5 min; The hot pressing conditions in step (4) are: hot pressing temperature 50-600° C., hot pressing pressure 0.01-20 MPa, and hot pressing time 0.1-48 h.

8. A thermally conductive aramid insulation paper-based material, characterized in that: It is prepared by the method according to any one of claims 1 to 7.

9. Use of the thermally conductive aramid insulation paper-based material according to claim 8 in insulation materials.

10. Use of the thermally conductive aramid insulation paper-based material according to claim 8 in the fields of electrical equipment, electronic information, aerospace or automobile industry.

Citation Information

Patent Citations

  • Heat conduction type aramid nano insulation paper and preparation method thereof

    CN108978328A

  • A kind of thermally conductive and insulating industrial aramid paper and preparation method thereof

    CN116289296B

  • Preparation method and application of high-thermal-conductivity aromatic polyamide fibers

    CN106498538A

  • Boron nitride nanosheet-embedded functional fiber and preparation method and application thereof

    CN118345520A

  • White high-thermal-conductivity para-aramid fiber and preparation method thereof

    CN118854479A

Cited By

  • Core-shell double-heat-conduction aramid fiber, heat-conduction insulation paper and preparation method and application of core-shell double-heat-conduction aramid fiber

    CN122406401A